Incidence and direct hospitalisation costs of hip fractures in Vilnius, capital of Lithuania, in 2010 - Tamulaitiene Marija; Alekna Vidmantas (BMC, 2012)
Abstract Background Few epidemiological data on hip fractures were previously available in Lithuania. The aim of this study was to estimate the incidence and hospital costs of hip fractures in Vilnius in 2010. Methods Data were collected from the medical charts of all patients admitted to hospitals in Vilnius (population, 548,835) due to new low-energy trauma hip fracture, during 2010. The estimated costs included ambulance transportation and continuous hospitalisation immediately after a fracture, which are covered by the Lithuanian healthcare system. Results The incidence of new low-energy trauma hip fractures was 252 (308 women and 160 men) per 100,000 inhabitants of Vilnius aged 50-years or more. There was an exponential increase in the incidence with increasing age. The overall estimated cost of hip fractures in Vilnius was 1,114,292 EUR for the year 2010. The greatest part of the expenditure was accounted for by fractures in individuals aged 65-years and over. The mean cost per case was 2,526.74 EUR, and cost varied depending on the treatment type. Hip replacement did not affect the overall mean costs of hip fracture. The majority of costs were incurred for acute (53%) and long-term care (35%) hospital stays, while medical rehabilitation accounted for only 12% of the overall cost. The costs of hip fracture were somewhat lower than those found in other European countries. Conclusion The data on incidence and costs of hip fractures will help to assess the importance of interventions to reduce the number of fractures and associated costs.